Psychological Assistance for Elderly Communities in Toket Village, Pamekasan - Yuliana Trisanti; Mohammad Nazir Arifin (Jurnal Pengabdian Indonesia, 2024)
The abstract The ultimate goal of every development boils down to improving the quality of human resources (HR). Human resources are both the subject and object of development, covering the entire human life cycle, from conception to the end of life. Therefore, the development of human quality must be an important concern. Based on the cycle above, it is necessary to make an effort to provide an alternative solution that can improve the performance of posbindu and activate sub-districts that do not yet have posbindu for the elderly, as well as increasing the happiness of the elderly group. Apart from that, activities are needed that can increase enthusiasm, skills and care for the elderly to provide comfort and happiness at the end of their lives. With technology transfer, the community provides genotyric care training for Posbindu cadres as partner communities. Therefore, accompanied by counseling activities and training on useful genotyric care, it can be effective, meaning that the training can be carried out for local elderly people who in turn can provide happiness and health for members of the elderly group as partners.